Sodium-glucose cotransporter 2 inhibitors attenuate vascular calcification by suppressing endoplasmic reticulum protein thioredoxin domain containing 5 dependent osteogenic reprogramming - Wu, Shaofa; Luo, Xiaolin; Chen, Yang; Wang, Zelan; Liu, Xi; Sun, Ning; Zhao, Junyong; Luo, Wenjian; Zhang, Jiawen; Tong, Xiaoyong; Huang, Lan; Liu, Chuan; et al. (Redox biology, 2024)
Vascular calcification is strongly linked to the development of major adverse cardiovascular events, but effective treatments are lacking. Sodium-glucose cotransporter 2 (SGLT2) inhibitors are an emerging category of oral hypoglycemic drugs that have displayed marked effects on metabolic and cardiovascular diseases, including recently reported vascular medial calcification. However, the roles and underlying mechanisms of SGLT2 inhibitors in vascular calcification have not been fully elucidated. Thus, we aimed to further determine whether SGLT2 inhibitors protect against vascular calcification and to investigate the mechanisms involved. A computed tomography angiography investigation of coronary arteries from 1554 patients with type 2 diabetes revealed that SGLT2 inhibitor use was correlated with a lower Agatston calcification score. In the vitamin D3 overdose, 5/6 nephrectomy chronic kidney disease-induced medial calcification and Western diet-induced atherosclerotic intimal calcification models, dapagliflozin (DAPA) substantially alleviated vascular calcification in the aorta. Furthermore, we showed that DAPA reduced vascular calcification via Runx2-dependent osteogenic transdifferentiation in vascular smooth muscle cells (VSMCs). Transcriptome profiling revealed that thioredoxin domain containing 5 (TXNDC5) was involved in the attenuation of vascular calcification by DAPA. Rescue experiments showed that DAPA-induced TXNDC5 downregulation in VSMCs blocked the protective effect on vascular calcification. Furthermore, TXNDC5 downregulation disrupted protein folding-dependent Runx2 stability and promoted subsequent proteasomal degradation. Moreover, DAPA downregulated TXNDC5 expression via amelioration of oxidative stress and ATF6-dependent endoplasmic reticulum stress. Consistently, the class effects of SGLT2 inhibitors on vascular calcification were validated with empagliflozin in intimal and medial calcification models. SGLT2 inhibitors ameliorate vascular calcification through blocking endoplasmic reticulum stress-dependent TXNDC5 upregulation and promoting subsequent Runx2 proteasomal degradation, suggesting that SGLT2 inhibitors are potentially beneficial for vascular calcification treatment and prevention. [Display omitted]